RELATIONSHIP BETWEEN SALT INTAKE AND GNRI IN ELDERLY DIALYSIS PATIENTS - Takaya Ozeki; Yazawa Masahiko; Tokunaga Saeko; Tanka Akio; Ryuge Akihiro; Makoto Yamaguchi; Ohyama Yukako; Haji Yoichiro; Imaizumi Takahiro; Tomino Tatsuhito; Shimizu Hideaki (The Korean Society of Nephrology, 2012)
While the recommended salt intake in dialysis patients is no more than 5 g/day in the KDOQI guideline, and 6 g/day in the JSH 2009 guideline, reducing salt consumption is difficult on the traditional Japanese diet. If a patient is malnourished, a low-salt diet poses a risk of aggravating the nutritional deficiency. Since elderly dialysis patients have nutritional deficiencies underlying their condition, the recommended low-salt diet may prevent these patients from receiving adequate nutrition. In the present study, factors associated with nutritional status in the elderly were assessed using the Geriatric Nutritional Risk Index (GNRI), which is considered to correlate with predictor of mortality among dialysis patients. Participating patients were anuric, had been maintained on dialysis for at least 2 years, and were 65 years of age or older. Factors assessed for their possible correlations with GNRI were primary disease, presence of spouse, presence of cohabiting family, weight gain, and estimated salt intake. We analyzed 36 patients (age 74.3±5.4 years, 50% males). GNRI was 90.9±7.7, and salt intake (8.02±1.94) correlated with GNRI (r=0.41, P=0.02). No correlations were detected for the presence of spouse or cohabiting family, which would have contributed to nutrition. In conclusion, the higher the salt intake, the better GNRI tended to be. This raised the possibility that it would be advantageous to avoid excessive salt restriction in nutritional training.